Sociodemographics and School Environment Correlates of Clustered Oral and General Health Related Behaviours in Tanzanian Adolescents - Kahabuka, Febronia Kokulengya; Mbawalla, Hawa Shariff; Mumghamba, Elifuraha Godson; Petersen, Poul Erik (International Journal of Child Health and Nutrition, 2019)
Objectives: To identify underlying clusters of general and oral health behaviours and acertain possible factors influencing the existence of the behaviours. Materials and Methods: A cross sectional study was conducted among 4,847 school adolescents aged 11 to 17 years. Data were collected using a structured questionnaire in Kiswahili inquiring about general and oral health related behaviours, socio-demographics and adolescents’ school relationship. Principal component analysis was employed to identify clusters of health behaviour. Frequency distribution for proportions, cross tabulations with chi-square and a two stage binary logistic regression were done. Results: Principal component analysis identified four clusters from twelve health behaviours; hygiene practices, dietary behaviours, cigarette smoking & alcohol consumption and sedentary related behaviours. Girls, OR 0.8 (95% CI 0.7, 0.9); secondary school attendees, OR 0.5 (95% CI 0.4, 0.7) and adolescents with good school relationship OR 0.7 (95% CI 0.6, 0.8) were less likely to smoke or use alcohol. Urban residents were less likely OR 0.8, (95% CI 0.7, 0.9) to report acceptable dietary behaviours. Adolescents whose fathers had secondary education or higher, were in secondary schools and had good school relationship were most likely to have acceptable hygiene behaviours, OR 1.4 (95% CI 1.2, 1.6), 1.6 (95% CI 1.1, 2.2) and 1.4 (95% CI 1.3, 1.7), respectively. Conclusion: Oral and general health behaviours of Tanzanian adolescents factored into four clusters with hygiene behaviours being most practiced and physical exercise the least. The clustered behaviours were influenced by socio-demographics and school environment.